IMPROVING PATRONAGE SERVICES FOR EXPECTANT MOTHERS AND CHILDREN, PRIMARY PREVENTION OF CONGENITAL ANOMALIES (American Journal of Research in Humanities and Social Sciences, 2024)
The prevalence of congenital anomalies among children, the study of risk factors and the development of a scientifically based system of measures to improve the patronage of future mothers and children to eliminate them.